2022
DOI: 10.1128/aem.02478-21
|View full text |Cite
|
Sign up to set email alerts
|

Viral Proteins Involved in the Adsorption Process of Deep-Purple, a Siphovirus Infecting Members of the Bacillus cereus Group

Abstract: The B. cereus group is a complex cluster of closely related species, among which certain strains can be pathogenic (i.e., Bacillus anthracis , Bacillus cereus sensu stricto , and Bacillus cytotoxicus ). Nowadays, phages are receiving increasing attention for applications in controlling and detecting such pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, particular Dit proteins, called evolved Dit (evoDit) proteins, have been identified in several phages. Besides their architectural role, these proteins are also implicated in phage adsorption as they harbor CBM able to bind to the host polysaccharides [ 121 , 122 ]. By being more exposed, evoDit proteins are thought to be involved in the first reversible binding, probably to increase the possibilities of host attachment in any virion orientations [ 116 ].…”
Section: The Phage Sidementioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, particular Dit proteins, called evolved Dit (evoDit) proteins, have been identified in several phages. Besides their architectural role, these proteins are also implicated in phage adsorption as they harbor CBM able to bind to the host polysaccharides [ 121 , 122 ]. By being more exposed, evoDit proteins are thought to be involved in the first reversible binding, probably to increase the possibilities of host attachment in any virion orientations [ 116 ].…”
Section: The Phage Sidementioning
confidence: 99%
“…Early characterization of the first tail protein, gp14 (YP_338197.1), revealed that it is involved in the phage γ adsorption and it was assumed that this protein was a tail fiber [ 170 ]. However, our recent analysis of the tail proteins of various siphoviruses infecting the B. cereus group (including those targeting B. anthracis ) showed that gp14 possesses a central CBM and is in fact an evolved Dit [ 122 ]. As for the second tail protein encoded by phage γ, gp15, its implication in the adsorption process was not assessed but analysis of different γ isolates highlighted that the gene encoding this protein is a hot spot for mutations, consistent with its involvement in phage adsorption [ 170 ].…”
Section: Adsorption Of Phages Infecting Gram-positive Bacteriamentioning
confidence: 99%
See 2 more Smart Citations